Effects of Sodium Metabisulfite Additives on Nursery Pig Growth - D. J. Shawk; S. S. Dritz; R. D. Goodband; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2018)
Sodium metabisulfite (SMB)-based feed additive efficacy was evaluated in 3 nursery pig growth experiments where pigs were fed diets containing low deoxynivalenol (<1.5 ppm; DON) concentrations. Pigs were weaned at approximately 22 d of age and randomly allotted to pens with one pen of 27 gilts and one pen of 27 barrows per fence line feeder, thus feeder was the experimental unit. In experiment 1, 2,268 pigs were used in a 35-d trial with 21 feeders per treatment. Experimental treatments included a control diet or the control with 0.50% SMB-based Product 1 (Defusion; Provimi, Brooksville, OH) fed in phase 1 and 0.25% fed in phases 2 and 3, then all pigs were fed a control diet for the last week of the study. Pigs fed Product 1 had greater (P<0.05) average daily gain (ADG), average daily feed intake (ADFI), and feed/gain ratio (F/G) compared to pigs fed the control diet from d 0 to 28. However, from d 28 to 35, the opposite response was observed, with pigs fed the control diet having greater ADG and improved F/G than pigs previously fed Product 1. Despite this response, pigs fed Product 1 were heavier (P<0.05) on d 35 than control-fed pigs. In experiment 2, 4,320 pigs were used in a 42-d trial with 8 or 16 feeders per treatment. Pigs were fed a control diet or diets with either SMB-based Product 1 or Product 2 (Nutriquest, Mason City, IA) at different concentrations and durations. Among the various treatments, Product 1 or Product 2 concentrations ranged from 0.50% initially to 0.25%, 0.15%, or none the last week of the study. Overall, pigs fed either of the additives at the highest concentrations and for the longest period of time had greater (P<0.05) ADG and ADFI compared to pigs fed the control diet, with those fed lower concentrations or shorter durations intermediate. In experiment 3, 2,808 pigs were used in a 28-d trial with 13 feeders per treatment. All pigs were fed a common diet for 7 d after weaning. Pigs were then either fed a control diet or diets containing Product 1 (0.50 and 0.25% from d 0 to 21 and 21 to 28 respectively), SMB (0.50 and 0.25% from day 0 to 21 and 21 to 28 respectively) or 0.25% SMB from day 0 to 28. Overall, pigs fed Product 1 or high SMB diets had greater (P<0.05) ADG compared to pigs fed low SMB or control diets. Collectively, these studies suggest that in diets with low DON concentrations, these SMB-based products increased ADG compared to pigs fed control diets.
Keywords: deoxynivalenol; nursery pig; preservative; sodium metabisulfite